1982
DOI: 10.1115/1.3138355
|View full text |Cite
|
Sign up to set email alerts
|

Turbulent Stresses in the Region of Aortic and Pulmonary Valves

Abstract: The specific features of turbulent flow that are likely to be damaging to the blood cells and platelets are the stresses which are intrinsic to turbulence, known as Reynolds stresses. These include normal stresses as well as shear stresses. The purpose of this study is to determine the magnitude of the turbulent stresses that may occur during ejection in the vicinity of normal and diseased aortic valves near normal pulmonary valves. Both Reynolds normal stresses and Reynolds shear stresses were calculated from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0

Year Published

1994
1994
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(13 citation statements)
references
References 0 publications
1
12
0
Order By: Relevance
“…The stress accumulation calculation was then performed by a summation of the instantaneous product of this scalar value of the total stress and the exposure time between successive nodal points along the platelet trajectory: σ × ∑ Δt (6) where Dt is the time step.…”
Section: Y Alemu and D Bluestein 680mentioning
confidence: 99%
See 1 more Smart Citation
“…The stress accumulation calculation was then performed by a summation of the instantaneous product of this scalar value of the total stress and the exposure time between successive nodal points along the platelet trajectory: σ × ∑ Δt (6) where Dt is the time step.…”
Section: Y Alemu and D Bluestein 680mentioning
confidence: 99%
“…Patients with MHV may develop thromboembolic complications (2). Nonphysiologic flow patterns are characterized by elevated shear stresses, with portions of the flow cycle becoming turbulent (3)(4)(5)(6). MHVs may induce jet flow, elevated shear stresses, areas of flow separation and recirculation, shed vortices, and turbulence (7).…”
mentioning
confidence: 99%
“…Hydraulic models, simulating the aortic valve, have demonstrated flow recirculation and eddy currents that swirl behind the flexible cusps during rapid flow through the valve orifice. 24 In the aortic outlet, ␤-gal activity was restricted to the valves and was undetectable in the vessel wall downstream ( Figure 3A). Sectioning through the outflow tract has shown that tie1 promoter is exclusively expressed in endothelial cells lining the inner aspect of the cup-shaped cusps but not in endothelial cells at the outer aspect of the same leaflet ( Figures 3B and 3C).…”
mentioning
confidence: 98%
“…In some cases, they overstimulate platelet thrombosis which then accelerate atherosclerosis as reported in Stein et al . [3]. On the other hand, the intimal thickening that causes the remodelling of the vessel wall relates to the presence of the low shear stresses at the throat of the stenosis, Ku et al .…”
Section: Introductionmentioning
confidence: 99%